Changes in the texture, physicochemical properties and volatile compound profiles of fresh Kashar cheese (<90 days) during ripening - Eroglu, Ali; Toker, Omer Said; Dogan, Mahmut (WILEY, 2016)
In this study, four different fresh Kashar cheese samples were ripened for 90 days. The physicochemical properties, texture attributes, fatty acid composition and volatile compound profiles of the samples were measured every 30 days of ripening. The texture properties of the cheese samples were significantly affected by the duration of the ripening period. The results of this study highlighted that texture parameters as a function of ripening period should be considered for both fresh and aged Kashar cheeses to determine the ripening period as they are very important for consumer acceptability and consumption of the end product.
Keywords: Fresh Kashar cheese; Ripening; Texture; Volatile compound; CONJUGATED LINOLEIC-ACID; CHEDDAR CHEESE; LOW-FAT; CHEMICAL-COMPOSITION; CHOLESTEROL CONTENT; BOVINE-MILK; PROTEOLYSIS; FLAVOR; Food Science & Technology